2015
DOI: 10.3332/ecancer.2015.560
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-p53 antibody as a tumour marker for colorectal cancer screening

Abstract: A 60-year-old Japanese man presented to our hospital for further investigation of an elevated serum anti-p53 antibody level. He was diagnosed with colon cancer and the tumour was surgically resected. Histological diagnosis of advanced colon cancer without lymph node involvement or distant metastasis was made. It was noteworthy that both serum carcinoembryonic antigen (CEA) and a fecal occult blood test that were performed preoperatively were non-diagnostic. This case highlights the potential usefulness of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…More than 50% of all human tumors have mutations in the tumor suppressor protein p53 and/or proteins that regulate its function (2). p53 status is a common biomarker in clinical studies of cancers, including breast (29), colorectal (72,150), gastric (61), and esophageal cancer (63), as well as other cancers (131). As a tumor suppressor, p53 has multiple roles in cell signaling.…”
Section: Inflammatory Response In Development and Progress Of Gi Cancermentioning
confidence: 99%
“…More than 50% of all human tumors have mutations in the tumor suppressor protein p53 and/or proteins that regulate its function (2). p53 status is a common biomarker in clinical studies of cancers, including breast (29), colorectal (72,150), gastric (61), and esophageal cancer (63), as well as other cancers (131). As a tumor suppressor, p53 has multiple roles in cell signaling.…”
Section: Inflammatory Response In Development and Progress Of Gi Cancermentioning
confidence: 99%
“…Sui et al reported that p53 could control cell invasion by inhibiting the NF-κB-mediated activation of Fascin [ 27 ]. Serum anti-p53 antibody was proved to be a useful biomarker for colorectal cancer screening [ 28 ]. p53 also plays critical roles in the transition from colorectal adenoma to carcinoma [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…CEA, CA125, CA19-9, AFP, M2 Pyruvate Kinase are common tumor markers also overexpressing in other type of cancers [48][49][50][51][52][53][54]. p53 antibodies usually indicates p53 gene mutations, which also happened in many type of cancers [55]. cytokeratin 18, RegIV are apoptosis related proteins indicating cell death during gastric cancer development [56,57].…”
Section: Serum Protein Biomarkers Of Gastric Cancermentioning
confidence: 99%